Harvard Data Science Review 2021
DOI: 10.1162/99608f92.edf2fc97
|View full text |Cite
|
Sign up to set email alerts
|

Individual Acceptance of Using Health Data for Private and Public Benefit: Changes During the COVID-19 Pandemic

Abstract: While the COVID-19 pandemic has been devastating, data collected in this context has unprecedented opportunities for data scientists. The stunning breadth of data obtained through new gathering systems put in place to manage the pandemic offers a richly textured view of a transformed world. Looking forward, privacy researchers worry that these new data-gathering systems risk running afoul of societal norms regarding the flow of information. Looking back at pre-pandemic public preferences with respect to data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
3
18
4
Order By: Relevance
“…On balance, it would appear that during the COVID-19 period Australians have become more trusting of organizations with regards to data privacy and less concerned about their own personal information and data. An important finding that is slightly different to that found in Gerdon et al (2021) is that in Australia trust in institutions increased regardless of their relevance to the pandemic itself. Combined, the two studies help to add nuance to the contextual integrity theory outlined in Gerdon et al (2021).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…On balance, it would appear that during the COVID-19 period Australians have become more trusting of organizations with regards to data privacy and less concerned about their own personal information and data. An important finding that is slightly different to that found in Gerdon et al (2021) is that in Australia trust in institutions increased regardless of their relevance to the pandemic itself. Combined, the two studies help to add nuance to the contextual integrity theory outlined in Gerdon et al (2021).…”
Section: Discussioncontrasting
confidence: 77%
“…An important finding that is slightly different to that found in Gerdon et al (2021) is that in Australia trust in institutions increased regardless of their relevance to the pandemic itself. Combined, the two studies help to add nuance to the contextual integrity theory outlined in Gerdon et al (2021).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Among studies using the CI framework, some have applied it to investigate users' perception of applications and data handling practices concerning COVID-19. In 2019, Gerdon et al [26], for example, conducted a CI-based longitudinal study in Germany, before the pandemic, examining people's acceptance of using individual health data during a pandemic, for public health or for private purposes. In 2020, in the wake of the pandemic, they were able to perform another such (opportunistic) study.…”
Section: Studying Privacy Through Contextual Integritymentioning
confidence: 99%
“…This study also reported that increased confidence in government institutions 1 explained an increase in trust in them to maintain data privacy between October 2018 and May 2020 (Biddle et al, 2020). However, it should be noted that research in Germany suggests that public acceptance of the use of individual health data to combat pandemics increased but for other scenarios the acceptance of the use of health data did not change over time (Gerdon et al, 2021).…”
Section: Public Trust and Social Licencementioning
confidence: 99%